2022
DOI: 10.1055/s-0042-1756690
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chronic Periodontitis with Helicobacter pylori Infection in Stomach or Mouth: A Systematic Review and Meta-Analysis

Abstract: Helicobacter pylori (H. pylori) infection and periodontitis are both inflammatory conditions associated with systemic diseases. Researchers have attempted to investigate the correlation between them. This systematic review and meta-analyses were conducted to investigate the association of H. pylori infection in the stomach and/or in subgingival plaque and gingival crevicular fluid with chronic periodontitis. The protocol was created according to the Preferred Reporting Items for Systematic review and Meta-Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Furthermore, chronic colon inflammation (colitis) leads indirectly to periodontitis by altering specific metabolic pathways (20). Additionally, Helicobacter pylori (H. pylori) stomach infection was suggested to be present in chronic periodontitis patients, CANCER DIAGNOSIS & PROGNOSIS 3: 189-193 (2023) but their exact relation is under investigation (21). In conjunction, apical periodontitis is the result of chronic endodontic inflammation mediated by bacteria of the Porphyromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chronic colon inflammation (colitis) leads indirectly to periodontitis by altering specific metabolic pathways (20). Additionally, Helicobacter pylori (H. pylori) stomach infection was suggested to be present in chronic periodontitis patients, CANCER DIAGNOSIS & PROGNOSIS 3: 189-193 (2023) but their exact relation is under investigation (21). In conjunction, apical periodontitis is the result of chronic endodontic inflammation mediated by bacteria of the Porphyromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori is a Gram‐negative spiral bacterium that is commonly believed to be closely associated with the occurrence and development of gastritis and stomach ulcers. Patients with periodontitis may have a higher rate of H. pylori infection (Tsimpiris et al, 2022). Studies have shown that H. pylori arrests human periodontal ligament fibroblasts in the G2 phase of the cell cycle and promotes apoptosis (Li et al, 2019).…”
Section: Effect Of Periodontal Microenvironment On the Death Of Pdlcsmentioning
confidence: 99%